Fiqih al-Hadits lil-Imam Malik fi Kitabihi “Al-Muwatta”: Syarah Hadits “Fiman Adraka Rak'atan” Namuzajan: فقه الحديث للإمام مالك في كتابه “الموطأ “: شرح حديث “فيمن ادرك ركعة” نموذجا - Sofyan, Nur Baety (El-Sunan: Journal of Hadith and Religious Studies, 2024)
This study aims to delve into the jurisprudence of hadith in the book “Al-Muwatta” by Imam Malik, with a specific focus on the explanation of the hadith “Man Adraka Rak`atan” as an example. An inductive and analytical approach is employed to elucidate several concepts, including the understanding of Imam Malik, the significance of the book “Al-Muwatta”, and the application of hadith jurisprudence in the book. The research begins with an explanation of Imam Malik and his book “Al-Muwatta”, as well as an introduction to the concept of hadith jurisprudence. The hadith jurisprudence method used by Imam Malik in “Al-Muwatta” is analyzed through the study of the hadith “Man Adraka Rak`atan”. The study concludes by presenting the main findings and citing the references used as the theoretical foundation. The findings reveal two main points: first, the understanding of hadith jurisprudence as the process of extracting legal rulings from hadith texts in accordance with Islamic jurisprudential principles; second, the application of hadith jurisprudence in the book “Al-Muwatta” by Imam Malik, which includes the methods used and other principles such as the authenticity of transmission, consistency in avoiding contradictions, and comprehension in line with the textual meaning. ABSTRAK Penelitian ini bertujuan untuk mendalami fikih hadis dalam kitab “Al-Muwatta” karya Imam Malik, dengan fokus pada penjelasan hadis “Man Adraka Rak`atan” sebagai contoh. Pendekatan induktif dan analitis digunakan untuk memperjelas beberapa konsep, termasuk pemahaman tentang Imam Malik, pentingnya kitab “Al-Muwatta”, dan penerapan fikih hadis dalam kitab tersebut. Penelitian dimulai dengan penjelasan mengenai Imam Malik dan kitab “Al-Muwatta”, serta pengenalan konsep fikih hadis. Metode fikih hadis yang digunakan oleh Imam Malik dalam “Al-Muwatta” dianalisis melalui studi terhadap hadis “Man Adraka Rak`atan”. Penelitian ini diakhiri dengan menyajikan hasil-hasil utama yang dicapai dan menyebutkan referensi yang digunakan sebagai landasan teoritis. Hasil penelitian mengungkapkan dua hal utama: pertama, pengertian fikih hadis sebagai proses mengekstraksi hukum-hukum dari teks hadis sesuai dengan prinsip-prinsip fikih Islam; kedua, penerapan fikih hadis dalam kitab “Al-Muwatta” karya Imam Malik, yang meliputi metode yang digunakan dan kaidah-kaidah lainnya seperti keaslian transmisi, keamanan dari pertentangan, dan pemahaman sesuai dengan makna teks.